Detection of gene variants associated with recessive limb–girdle muscular weakness and Pompe disease in a global cohort of patients through the application of next-generation sequencing analysis - Bevilacqua, Jorge Alfredo; Al-Salti, Abdullah Mohammed; Al Madani, Abubaker; Alves da Fonseca, Armando; Durmus, Hacer; Chai, Josiah; Alshehri, Ali; Ribeiro, Márcia Gonçalves; Sgobbi, Paulo; Nikitin, Sergey S.; Vargas, Steven; Furtado, Adriana; et al. (Frontiers in Genetics, 2024)
IntroductionHereditary myopathies arise due to numerous pathogenic variants occurring in distinct genes, which amount to several hundred. Limb–girdle muscular dystrophies (LGMDs) constitute a heterogeneous group of neuromuscular disorders involving more than 30 genes. Clinically, LGMD is characterized by limb–girdle muscular weakness (LGMW). Late-onset Pompe disease is an important disorder with a differential diagnosis for LGMD, where next-generation sequencing (NGS) plays a crucial role in accurate and prompt diagnosis. The sensitivity and specificity of a 10-gene NGS panel have been previously evaluated for the prevalent forms of recessive LGMD (LGMD-R) and Pompe disease in Latin American patients with LGMW of unknown cause. This project aims to identify the regional relative prevalence of frequent LGMD-R subtypes and Pompe disease in a larger geographic area and to diagnose patients with LGMW by identifying genetic variants of LGMD-R and Pompe disease.Methods and ResultsThis 21-country multicentric analysis enrolled 2,372 patients with LGMW from 2017 to 2018. Sequencing analysis was performed using the Illumina NextSeq 500 system, and variant interpretation was performed according to the American College of Medical Genetics and Genomics guidelines. Pathogenic or likely pathogenic variants were seen in 11% of patients (n = 261). Among the positive cases, NGS effectively diagnosed 86.2% and 13.8% of patients with LGMD and Pompe disease, respectively. The most prevalent pathogenic acid α-glucosidase (GAA) variant identified was c.-32-13T > G.ConclusionThe study adds to the knowledge of the relative occurrence of various subtypes of LGMD worldwide. The inclusion of GAA in the NGS panel to investigate patients with LGMW is a powerful diagnostic approach to screen for late-onset Pompe disease.